Design Computing and Cognition '18 - Gero, John S. (Springer International Publishing : Imprint: Springer, 2019)
This is the proceedings of the Eighth International Conference on Design Computing and Cognition (DCC'18) held at the Polytecnico di Milano in Italy. This volume presents both advances in theory and applications and demonstrates the depth and breadth of design computing and design cognition. Design thinking, the label given to the acts of designing, has become a paradigmatic view that has transcended the discipline of design and is now widely used in business and elsewhere. As a consequence there is an increasing interest in design research. This volume contains papers that represent the state-of-the-art research and developments in design computing and design cognition. This book is of particular interest to researchers, developers and users of advanced computation in design and those who need to gain a better understanding of designing that can be obtained through empirical studies. .